Multiscale scenarios for nature futures - Rosa, Isabel M. D. (2017)
Scenarios are powerful tools toenvision how nature might respondto different pathways of futurehuman development and policy choices1.Most scenarios developed for globalenvironmental assessments have exploredimpacts of society on nature, such asbiodiversity loss, but have not includednature as a component of socioeconomicdevelopment2. They ignore policyobjectives related to nature protectionand neglect nature?s role in underpinningdevelopment and human well-being.This approach is becoming untenablebecause targets for human developmentare increasingly connected with targetsfor nature, such as in the United Nations?Sustainable Development Goals. The nextgeneration of scenarios should explorealternative pathways to reach theseintertwined targets, including potentialsynergies and trade-offs between natureconservation and other developmentgoals, as well as address feedbacks betweennature, nature?s contributions to people,and human well-being. The developmentof these scenarios would benefit from theuse of participatory approaches, integratingstakeholders from multiple sectors (forexample, fisheries, agriculture, forestry)and should address decision-makersfrom the local to the global scale3, therebysupporting assessments being undertakenby the Intergovernmental Platformon Biodiversity and EcosystemServices (IPBES).